THE IMPACT OF USING ARTIFICIAL INTELLIGENCE IN ADMINISTRATIVE DECISION: A STUDY OF LEGITIMACY OF BALANCING SECURITY REQUIREMENTS (World Economics and Finance Bulletin, 2026)
The purpose of the study is to investigate administrative control via automated decisions issued by artificial intelligence systems. This study further led to an investigation and mapping of the challenges involved in compliance with administrative control by artificial intelligence system. A socio-legal study approach was adopted based on library-based comparative approach is functional, focusing on the way each legal system response to a similar set of issues raised by AI-based automated decisions and not so much finding similarities through formal legal texts. This approach helps to identify functional alternatives, regulatory lacunae and best practices that can be transferred across borders regarding the impact administrative control by artificial intelligence system the findings revealed that, for Iraq to meet the AI obligation, they must overcome challenges including cost and complexity. Nevertheless, these costs are less expensive than the drawbacks assessed for non-compliance. Following judicial review automated decision issued by artificial intelligence system can help the Iraqi judiciary grow. However, it is difficult and expensive to comply with these requirements. The current research hopes that the AI regulatory authorities of French and Iraq will adopt more effective measures for efficient compliance with AI.
Keywords: Accountability; Artificial intelligence; Automated decision